ANALISIS KAPASITAS UPLINK DAN DOWNLINK SISTEM SELULAR WCDMA ATAS KETIDAKSEMPURNAAN SEKTORISASI SEL - Santoso, Gatot; Kristiyana, Samuel (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
In this research analyzes the connection Wideband Code Division Multiple Access (WCDMA) for uplink and downlink with imperfect sectorization. Because all channels are on the same frequency, so when the active user increases, the performance of system will decrease. In other words, it causes the capacity of system will decrease. In CDMA terminology, the other frequency of Mobile Station (MS) will get effect to the active MS. The co-channel interference can be decrease with splitting the cell into several sectors. It is called the sectorization. But the sectorization can work well because the antenna radiation can’t make the perfect angle and also there is existance of side lobe of radio frequency. The results show, the imperfect sectoration overlap angle between each neighboring sector decreases the capacity system cause more interference to overlapping sector pair. The knowledge gained is to neduce the large overlap angle and we can make the prediction the loss in cell capacity caused by interference.